Antibodies to a Surface-Exposed, N-terminal Domain of Aggregation Substance Are Not Protective in the Rabbit Model of Enterococcus faecalis Infective Endocarditis - McCormick, John K. (American Society for Microbiology, 2001)
The aggregation substance (AS) surface protein from Enterococcus faecalis has been implicated as an important virulence factor for the development of infective endocarditis. To evaluate the role of antibodies specific for Asc10 (the AS protein from the conjugative plasmid pCF10) in protective immunity to infective endocarditis, an N-terminal region of Asc10 lacking the signal peptide and predicted to be surface exposed (amino acids 44 to 331; AS(44–331)) was cloned with a C-terminal histidine tag translational fusion and expressed from Escherichia coli. N-terminal amino acid sequencing of the purified protein revealed the correct sequence, and rabbit polyclonal antisera raised against AS(44–331) reacted specifically to Asc10 expressed from E. faecalis OG1SSp, but not to other proteins as judged by Western blot analysis. Using these antisera, flow cytometry analysis demonstrated that antibodies to AS(44–331) bound to a surface-exposed region of Asc10. Furthermore, antibodies specific for AS(44–331) were opsonic for E. faecalis expressing Asc10 in vitro but not for cells that did not express Asc10. New Zealand White rabbits immunized with AS(44–331) were challenged intravenously with E. faecalis cells constitutively expressing Asc10 in the rabbit model of experimental endocarditis. Highly immune animals did not show significant differences in clearance of organisms from the blood or spleen or in formation of vegetations on the aortic valve, in comparison with nonimmune animals. Although in vivo expression of Asc10 was demonstrated by immunohistochemistry, these experiments provide evidence that immunity to Asc10 does not play a role in protection from experimental infective endocarditis due to E. faecalis and may have important implications for the development of immunological approaches to combat enterococcal endocarditis.